2015
DOI: 10.1108/meq-05-2014-0063
|View full text |Cite
|
Sign up to set email alerts
|

The impact of financial development, economic growth and energy consumption on environmental degradation

Abstract: Purpose – The purpose of this paper is to investigate the impact of financial development, economic growth and energy consumption on environment degradation for Indian economy by using the time series data for the period 1971-2011. Design/methodology/approach – The stationary properties of the variables are checked by ADF, DF-GLS, PP and Ng-Perron unit root tests. The long-run relationship is examined by implementing the Autoregressive D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(76 citation statements)
references
References 52 publications
(36 reference statements)
14
51
0
Order By: Relevance
“…Keeping other things constant, carbon emissions are expected to increase by 0.0428% as a result of 1% increase in financial development. This finding is similar to the study by Zhang (2011) on China and Sehrawat et al. (2015) on India as both of these studies reported a positive impact of financial development on carbon emissions.…”
Section: Analysis Findingssupporting
confidence: 89%
“…Keeping other things constant, carbon emissions are expected to increase by 0.0428% as a result of 1% increase in financial development. This finding is similar to the study by Zhang (2011) on China and Sehrawat et al. (2015) on India as both of these studies reported a positive impact of financial development on carbon emissions.…”
Section: Analysis Findingssupporting
confidence: 89%
“…Researchers used different econometric techniques for identifying causality among different macroeconomic variables. The present study follows the econometric technique used by Sehrawat and Mohapatra (2015) and for analysis.…”
Section: Model Specificationmentioning
confidence: 99%
“…Different researchers have found divergent results in the growth–energy use nexus due to time or methodological differences, patterns of energy or economy, and heterogeneous climatic conditions (Shahbaz, Tiwari, et al, 2013). However, there is a direct link between energy consumption and environmental degradation (Boutabba, 2014; Destek, Balli, & Manga, 2016; Jalil & Feridun, 2011; Jamel & Derbali, 2016; G. Li et al, 2016; Omri, 2013; Saboori & Sulaiman, 2013; Sanderson et al, 2013; Sehrawat et al, 2015; Tamazian et al, 2009). Continuous consumption of non‐renewable energy sources (oil, coal, and gas) is resulting in an alarming increase in global warming and depletion of the ozone layer.…”
Section: Theoretical Review and Hypotheses Developmentmentioning
confidence: 99%
“…Of all the pollutants, CO 2 is empirically the most influential element in global warming (Pachauri et al, 2014). The majority of scientists have depicted different shapes (inverted U‐shaped, U‐shaped, or N‐shaped) in the relationship between economic growth and environmental degradation (Alkhathlan, Alam, & Javid, 2012; Bekhet et al, 2017; He, Xu, Shen, Long, & Chen, 2017; Jalil & Feridun, 2011; Jayanthakumaran, Verma, & Liu, 2012; Saboori & Sulaiman, 2013; Sehrawat et al, 2015; Zi, Jie, & Hong‐Bo, 2016). CH 4 is the second most influential GHG, and it is 25 times more potent than CO 2 .…”
Section: Theoretical Review and Hypotheses Developmentmentioning
confidence: 99%